“O bicho-papão na escola”: a proposta curricular do município de Fortaleza para Educação Infantil no processo da desescolarização de crianças de 0 a 5 anos - Ferreira, Marcela Figueira (2020)
The main objective of this research is to investigate, in the curricular proposal for early childhood education in the city of Fortaleza, unschooling aspects and the denial of scientific knowledge, in the first stage of basic education. It addresses the political and historical path that culminated in the development of the BNCC for Early Childhood Education and how the municipality of Fortaleza absorbs neoliberal ideas to build its local proposal. With theoretical support in the historical-critical pedagogy, it identifies in the Common Curriculum Proposal for Early Childhood Education in the city of Fortaleza desescolarizados aspects because, it is based on hegemonic theories with neoliberal and postmodern character. With bibliographic and documentary methodology, it is theoretically based on authors of historical-critical pedagogy such as SAVIANI (1996, 1997, 2013), DUARTE (2011, 2015, 2017) and authors who dedicated themselves to studying historical-critical pedagogy, specifically, in area of Early Childhood Education as ARCE (2012, 2013), PASQUALINI (2018, 2020). It bases the study on historical-dialectical materialism, proposing, based on reality, to analyze the most abstract concepts and at the point of arrival understand it as the product of a totality of different relations and determinations. It was possible to conclude the mastery of learning to learn pedagogies in every curriculum proposal for early childhood education, both at the national level (BNCC) and at the local level. The search to remove early childhood education from schooling characteristics is contradictory to the struggle for its recognition as basic education and a danger today with home education projects, such as homeschooling. We aim for the children of the working class a quality education through the socialization of the cultural heritage of humanity, respecting the specificities of early childhood education, in order to build a curriculum that aims at human formation and meets the revolutionary interests of the working class.